A preliminary checklist of the Coccinellidae of Bhutan (Insecta: Coleoptera) - Dorji, Cheten; Loday, Phuntsho; Vorst, Oscar (Zootaxa, 2019)
An annotated distributional checklist of the Coccinellidae of Bhutan is presented, enumerating 91 species, 17 of which are here recorded for the first time: Shirozuella tibetina Wang, Ge & Ren, 2012, Jauravia limbata (Motschulsky, 1858), Scymnus bourdilloni (Kapur, 1958), Illeis confusa Timberlake, 1943, Calvia albida Bielawski, 1972, Harmonia expalliata Sicard, 1913, H. octomaculata (Fabricius, 1781), H. sedecimnotata (Fabricius, 1801), Micraspis allardi (Mulsant, 1866), M. discolor (Fabricius, 1798), M. univittata (Hope, 1831), Oenopia adelgivora Poorani, 2002, O. billieti (Mulsant, 1853), O. smetanai Canepari, 1997, Afissula mysticoides (Sicard, 1913), Henosepilachna processa Li & Cook, 1961 and H. septima (Dieke, 1947). One species, Propylea japonica (Thunberg, 1781), has to be removed from the list.                Nine species and two subspecies are hitherto only reported from the territory of Bhutan. The Bhutanese coccinellid fauna is still insufficiently known.